Efficacy and safety of combining re-irradiation with bevacizumab compared to bevacizumab alone in the management of recurrent high-grade gliomas: a meta-analysis and systematic review - Ali Hammed; Almonzer Al-Qiami; Ali Hasan; Gregor Richter; Asmaa Zakria Alnajjar; Josef Rosenbauer; Karel Kostev; Omar Ismail; Veit Braun; Christian Tanislav (Therapeutic Advances in Neurological Disorders)
Background: There is currently no established standard of care for recurrent glioblastoma (GBM). Re-irradiation (re-RT) and Bevacizumab (BEV) are both used in salvage treatment, but their combined efficacy remains uncertain. Objectives: To evaluate whether combining re-irradiation with BEV improves survival outcomes compared to BEV alone in patients with recurrent high-grade gliomas (rHGG). Design: Systematic review and meta-analysis of two-arm clinical trials. Data sources and methods: A comprehensive literature search was conducted in Scopus, PubMed, Web of Science, and the Cochrane Library up to April 2024. Two independent reviewers assessed studies for eligibility and extracted data. Study quality was evaluated using the ROBINS-I and ROBINS-II tools. The primary outcome was overall survival (OS); secondary outcomes included progression-free survival (PFS), toxicity, and prognostic factors. Results: The meta-analysis demonstrated a significant improvement in OS with combined BEV and re-irradiation compared to BEV alone (hazard ratio (HR) 0.69, 95% confidence interval (CI: 0.56–0.85); p  = 0.0005), corresponding to a 31% reduction in the risk of death. PFS also improved significantly (HR 0.64, 95% CI (0.45–0.90); p  = 0.01). No significant increase in grade 3 toxicities was observed with the combination therapy. Subgroup analyses indicated that younger age and female gender were statistically associated with better OS, though the effect of age was modest and male gender was linked to poorer survival. Karnofsky performance status significantly influenced survival. Pulsed versus non-pulsed re-irradiation showed no differential effect on outcomes. Conclusion: The combination of re-irradiation and BEV significantly improves both OS and PFS in patients with rHGG, without increasing severe toxicity. These findings support the safety and efficacy of the combined approach. Prospective trials are warranted to guide standardized treatment protocols. Trial registration: This review was prospectively registered with PROSPERO (CRD42023463183).